Education and Social Justice: presentation (Research, Society and Development, 2021)
Social justice has never been so much in vogue as in this epidemic scenario of COVID-19, theinequalities were accentuated and publicized in different media,presenting the diverse effects in specific groups and contexts, due to associated factorsto socioeconomic inequalities, due to racist, misogynistic, xenophobic andhomolesbotransphobics among others. The proposed dossier will receive contributions in Portuguese,English and Spanish on the problematization of Education for Social Justice, identifyingpraxis related to race and traditional peoples, gender, sexual orientation, sexuality,refugees and immigration processes from perspectives such as critical racial theory (CRT),intersectionalities, decolonialities, feminist studies, anti-racism and otherspedagogies that contribute to social transformation and construction of an education fordemocracy and, consequently, a more equitable society